Paradoxical mortality differential of HDL cholesterol - Jyotishman Mukhopadhyay; Debayan Mallik; Sughandha Garg (Asian Journal of Medical Sciences, 2023)
High-density lipoprotein (HDL) cholesterol has been known for ages to be cardio-protective due to its defensive action against genesis of atherosclerosis. Increasing the serum HDL cholesterol (HDL-C) as a prospective potential to prevent coronary heart disease could not prove beneficial in human trials that put forward a major concern about the role and functional contribution of HDL-C in human health. Many observational studies indicated that extreme high value of serum HDL-C is often associated with high cardiovascular mortality; therefore could be considered as detrimental for healthy survival. Furthermore, observational and genetic studies revealed a possible link between extreme low serum HDL-C and development of common noncardiovascular diseases such as infectious disease, autoimmune disorder, malignancy, type-2 diabetes, kidney, and pulmonary diseases. This review endeavors to update on the various reasons of mortality observed with extreme values of HDL-C reflected in the recent studies along with the probable role of HDL-C in the pathogenesis of these ailments.